Tourist Attractiveness of Russian Territories in the Online Network Space. Estimates and Interests of Consumers of Tourist Services - FROLOVA, Elena V.; RYABOVA, Tatyana M.; ROGACH, Olga V. (Journal of Environmental Management and Tourism, 2019)
The article discusses the assessment of the tourist attractiveness of Russian territories presented in the online network space. The empirical base of the study was the results of the content analysis of the reviews of tourists posted on the Internet. Media content, representation of tourism products in social networks contribute to the consolidation of new images, stereotypes and fashion in tourism practices of various social groups, form the expectations and interests of consumers of tourism services. The results of the research showed the actualization of the needs of tourists in authentic products, tourist impressions associated with national traditions, local color, historical artifacts. Tourists' expectations are focused on visualization of impressions, aesthetic appeal of tourist attraction objects. The emphasis on the hospitality of local residents, the recreation of historical traditions, identity and cultural diversity are promising areas of the formation of a popular tourist product.